Capital-Account Liberalization, the Cost of Capital, and Economic Growth - Henry, Peter Blair (American Economic Review, 2003)
Three things happen when emerging economies open their stock markets to foreign investors. First, the aggregate dividend yield falls by 240 basis points. Second, the growth rate of the capital stock increases by an average of 1.1 percentage points per year. Third, the growth rate of output per worker rises by 2.3 percentage points per year. Since the cost of capital falls, investment booms, and the growth rate of output per worker increases when countries liberalize the stock market, the increasingly popular view that capital account liberalization brings no real benefits seems untenable.